2021
DOI: 10.1016/j.apenergy.2021.117843
|View full text |Cite
|
Sign up to set email alerts
|

Peak oil and the low-carbon energy transition: A net-energy perspective

Abstract: Global gross and net-energy of oil liquids production is determined from 1950 to 2050.• Energy required for production is estimated to be 15.5% of the actual gross energy.• Oil liquids become a limit to a rapid and global low-carbon energy transition.• The peak supply vs. peak demand dispute needs to be re-examined.• Focus should be put instead on net-energy transition and wise energy consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 182 publications
(202 reference statements)
0
23
0
5
Order By: Relevance
“…Firstly, the realistic EROI of fossil fuels has been often overestimated by only focusing on EROI values calculated at point of extraction. For instance, while the EROI of crude oil at the well head may, in some cases, have been as high as 100 during its initial "golden age" [249], [250], detailed analyses have shown that this value has been steadily declining over time as a consequence of depletion [251], [252], [253], [254]. Even more importantly, the many subsequent energy investments required along the crude oil supply chain to process and deliver it in the form of readily usable energy carriers have always reduced the resulting EROI values at point of use to well below 10, irrespective of the initial EROI at point of extraction [250], [255].…”
Section: A Energy Return On Investmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the realistic EROI of fossil fuels has been often overestimated by only focusing on EROI values calculated at point of extraction. For instance, while the EROI of crude oil at the well head may, in some cases, have been as high as 100 during its initial "golden age" [249], [250], detailed analyses have shown that this value has been steadily declining over time as a consequence of depletion [251], [252], [253], [254]. Even more importantly, the many subsequent energy investments required along the crude oil supply chain to process and deliver it in the form of readily usable energy carriers have always reduced the resulting EROI values at point of use to well below 10, irrespective of the initial EROI at point of extraction [250], [255].…”
Section: A Energy Return On Investmentmentioning
confidence: 99%
“…Similar, albeit perhaps not as drastic, EROI reductions from point of extraction to point of use also affect all other fossil fuels such as coal and gas. Furthermore, a substantial decline of fossil oil and gas EROI is projected [252], [253], [255] for the decades to come [251], [252]. The decline of the EROI of nonrenewable resources is an unavoidable effect of depletion, a phenomenon that has been dynamically modeled [254].…”
Section: A Energy Return On Investmentmentioning
confidence: 99%
“…On the one hand, we can assume that future energy reduction solutions will have similar benefits to the current ones-that they will enable monetary savings, will be modern, and will reduce GHG emissions; on the other, reversing the current trend of ever-growing energy demand will require much more radical action than is currently being taken. Steps to reduce energy consumption might become a necessity in order to enable actual reductions in global GHG emissions and extend the time in which we have access to relatively affordable fossil fuels, which allows us to transform the economy to use new energy sources [4]. Decisive action to reduce energy consumption might serve to alter public opinion on such measures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts by the international community to reduce the scale of GHG emissions (Kyoto Protocol 1997; Paris Agreement 2015), global consumption of fossil fuels is increasing, and the risk of dangerous consequences of climate destabilization is growing [3]. Additionally, there is a threat that the availability of fossil fuels may begin to decline rapidly in the coming decades, due to the exponentially increasing cost of extraction of these fuels, further reducing the available time to transition the economy to new energy sources [4].…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining electricity from fossil fuels releases enormous amounts of greenhouse gases and other pollutants into the atmosphere [3][4][5], not to mention destroying the landscape in vast spaces. It is estimated that, in 2019, the energy sector was responsible for 77% of greenhouse gas emissions, followed by agriculture (11%), industrial processes and product use (9%), and waste management (3%) [6].…”
Section: Introductionmentioning
confidence: 99%